Hubungan Vitamin C dan Tingkat Kepatuhan Minum TTD dengan Kadar HB pada Remaja Putri - Bela Novitasari; Dian Ayu Ainun Nafies; Miftahul Munir; Lilia Faridatul Fauziah (Inovasi Kesehatan Global, 2026)
Anemia is a common nutritional problem among adolescent girls and can affect health, learning ability, and the quality of future generations. Hemoglobin (Hb) levels can be influenced by dietary intake, such as folic acid and vitamin C, as well as consumption behaviors, including tea drinking habits and adherence to iron supplementation (TTD). This study aimed to examine the relationship between folic acid intake, vitamin C intake, tea drinking habits, and adherence to TTD consumption with hemoglobin levels among adolescent girls in senior high schools in Tuban District. This study used a cross-sectional design with a sample of 325 respondents selected through probability sampling. Data on folic acid and vitamin C intake were obtained using a 24-hour dietary recall method, while tea drinking habits and adherence to TTD consumption were collected through questionnaires. Hemoglobin levels were measured directly using a hemoglobin testing device. Data analysis was performed using the Spearman correlation test. The results showed significant relationships between folic acid intake and hemoglobin levels, vitamin C intake and hemoglobin levels, adherence to iron supplementation and hemoglobin levels, and tea drinking habits and hemoglobin levels, with a negative direction of association. This study concludes that folic acid intake, vitamin C intake, tea drinking habits, and adherence to TTD consumption influence hemoglobin levels in adolescent girls. Efforts to prevent anemia should focus on improving dietary patterns, proper use of iron supplementation, and regulating tea drinking habits.